Predictability of depression severity based on posterior alpha oscillations. Issue 4 (April 2016) - Jiang, H.; Popov, T.; Jylänki, P.; Bi, K.; Yao, Z.; Lu, Q.; Jensen, O.; van Gerven, M.A.J.
Highlights: Distinct oscillatory activity differences between major depressive disorder (MDD) and healthy controls (HC) were identified. Posterior alpha power was found to be negatively related to depression severity. Bayesian linear regression provides a quantitative and objective estimation of depression severity. Abstract: Objective: We aimed to integrate neural data and an advanced machine learning technique to predict individual major depressive disorder (MDD) patient severity. Methods: MEG data was acquired from 22 MDD patients and 22 healthy controls (HC) resting awake with eyes closed. Individual power spectra were calculated by a Fourier transform. Sources were reconstructed via beamforming technique. Bayesian linear regression was applied to predict depression severity based on the spatial distribution of oscillatory power. Results: In MDD patients, decreased theta (4–8 Hz) and alpha (8–14 Hz) power was observed in fronto-central and posterior areas respectively, whereas increased beta (14–30 Hz) power was observed in fronto-central regions. In particular, posterior alpha power was negatively related to depression severity. The Bayesian linear regression model showed significant depression severity prediction performance based on the spatial distribution of both alpha ( r = 0.68, p = 0.0005) and beta power ( r = 0.56, p = 0.007) respectively. Conclusions: Our findings point to a specific alteration of oscillatory brain activity in MDD patients during rest as characterized from MEG data in terms of spectral and spatial distribution. Significance: The proposed model yielded a quantitative and objective estimation for the depression severity, which in turn has a potential for diagnosis and monitoring of the recovery process.